Taller 4 Calculo Iii
Taller 4 Calculo Iii
Taller 4 Calculo Iii
CALCULO III
DIANA CRUZ
HUGO CABEZAS
WILSON GIRALDO
SEMESTRE III
IDEAD
IBAGUE
2021
TALLER 4 - CALCULO III
1.
2
∫ ( 2 x+6 ) dx
−3
2 2
∫ ( 2 x+6 ) dx= 22x +6 x +C=x 2+ 6 x+C
−3
2
2
∫ ( 2 x+6 ) dx= x2 +6 x +C ] −3
−3
( 22 +6 ( 2 ) ) −( (−3 2 )+ 6 (−3 ) )
25
2.
2
∫ ( 7−3 x ) dx
−1
2 2 2
3x 3x
∫ ( 7−3 x ) dx=7 x− 2
+C=7 x−
2
+C
−1
]
2 2 2
3x
∫ ( 7−3 x ) dx=7 x− 2 +C
−1 −1
( 7 (2)−
3( 2)2
2 )(
− 7 (−1)−
3 (−1)2
2 )
33
2
3. M
∫ ( 3 x 2 +5 ) dx
1
4 4 4
∫ ( 3 x 2 +5 ) dx=3 ∫ x 2 dx+∫ 5 dx
1 1 1
3
3x
+ 5 x +C=x 3 +5 x+C
3
4
4
∫ ( 3 x 2 +5 ) dx= x 3 +5 x +C ] 1
1
78
4. M
∫ ( 2−9 x−4 x 2) dx
1
4 4 4 4
1 1 1 1
9 x2 4 x3
2 x− − +C
2 3
Ahora reemplazamos en laintegral definida :
]
4 2 3 4
9x 4x
∫ ( 2−9 x−4 x ) dx=2 x− 2 − 3 +C
2
1 1
( 2( 4)−
9( 4)2 4 (4)3
2
−
3
−¿ )
(−66− 2563 )−( −92 − 34 )
291
2
5. M
∫ ( 3 x +2 )2 dx=¿
1
4 4 4 4 4
1 1 1 1 1
9 x3 12 x 2
+ + 4 x+C=3 x 3 +6 x 2+ 4 x +C
3 2
4
4
∫ ( 9 x 2 +12 x+ 4 ) dx =3 x 3 +6 x 2+ 4 x +C ] 1
1
291
6. M
1
∫ √5 x dx=¿
4
1 1 1 1
()
3
+C= √ √ +C= √
2 3 3
x 2 5 x 2 5x
√5 +C
3 3 3
2
∫ √5 x dx= 2 √35 x
1 3
1
+C ] 4
4
( 2 √5(1) 2 √ 5(4)
)( )
3 3
−
3 3
−14 √ 5
3
7. M
4
∫ 2 x ( x +1 ) dx
1
4 4 4 4
1 1 1 1
3 2 3
2x 2 x 2x 2
+ +C= + x +C
3 2 3
( )( )
3 3
2(4 ) 2(1)
+(4)2 − +(1)2
3 3
57
8. M
∫ ( √ x−5 ) dx
2
4 4
1 1
4 4 4 1 4
3 3
2 2 2 2
x 10 x x 20 x
− + 25 x +C= − +25 x+C
2 3 2 3
2
x2 20 √ x 3
− + 25 x +C
2 3
]
4
x 2 20 √ x3
4
1 1
( 4 20 √ 4 1 20 √ 1
)( )
2 3 2 3
− +25 (4) − − +25(1)
2 3 2 3
(8− 20 √364 +100)−( 12 − 203√ 1 +25)
215
6
9. M
∫ ( 3 √ x +1 )( √ x−2 ) dx
1
1 1 1 1 1
+
2 2 2 2 2
3x −6 x + x −2=3 x−5 x −2
∫ (3 x−5 x −2 ) dx
4 1
2
( )
4 4 1
4 4 1 4
3∫ x dx −5∫ x dx−∫ 2 dx 2
1 1 1
3 3
2 2 2 2
3x 5x 3 x 10 x
− −2 x+C= − −2 x++ C
2 3 2 3
2
3 x 10 √ x
2 3
− −2 x +C
2 3
]
4
1 1
( 3(4)2 10 √ 4 3
2
−
3
−2(4) −
2
−
3 )(
3(1)2 10 √13
−2(1) )
(24− 803 −8)−( 32 − 103 −2)
−41
6
10. M
3
∫ 3 x 2 dx=27
0
3 3
3x
3∫ x dx=
2 3
+C=x +C
0 3
3 3
∫ 3 x 2 dx= 33x
3
+C ] 0
0
( )
3
3(3)
− ( 0)
3
27
11. M
3 3 3 3
−1 −1 −1 −1
3 2
3x 2x 3 2
− +3 x +C=x −x + 3 x +C
3 2
3
3
∫ ( 3 x 2−2 x+3 ) dx=x 3 −x2 +3 x +C ] −1
−1
32
12. M
∫ 3 √ x+1 dx=54
−1
8 8 1
−1
13. M
−1
∫ 8 x−3 dx=−3
−2
−1 −2
8x −4
8 ∫ x dx=
−3
+C=−4 x−2 +C= 2 +C
−2 −2 x
∫ 8 x−3 dx=¿ −4
−1
2
+C ] −2
−2 x
( −4
(−1)
2
−
−4
)(
(−2)
2 )
−3
14. M
∫ (2+3 √ x )dx=20
1
4 4 4 1
3
3 x2
+C=2 x+2 √ x +C
3
2 x+
3
2
∫ (2+3 √ x )dx=2 x +2 √ x 3 +C ] 1
4
15. M
7
1 1
∫( 3
dx=
10
2 x+ 3 )
7 7 7
u−1 −1
+C= +C
−1 u
1
Reemplazamos:− +C
x+ 3
]
7 7
∫ ( 1 )3 dx= x+3
−1
+C
2 x+ 3 2
( 7+3
−1
)−( 2+3
−1
)
1
10
16. M
∫ 4 √3 x dx=45
1
8 8 1 1
∫ 4 √ x dx=4 ∫ √ x dx=4 ∫ x
3 3 3
dx
1 1 4
()
4
3
x
+C=3 √ x 4 +C
3
4
4
3
∫ 4 √3 x dx=3 √ x 4 + C ] 1
3 8
( 3 √3 8 4 )−( 3 √3 1 4 )
45
17. M
∫
1
( x + x1 ) dx= 283
2
2
3 3 3
∫
1
( 2
x+
1
x 2 )
dx=∫ x dx +∫ x dx
1
2
1
−2
x3 1
− +C
3 x
]
3 3
∫
1
( 1
x
2 x3 1
x + 2 dx= − +C
3 x ) 1
( 33 1
3 3
13 1
− − −
3 1 )( )
28
3
18. M
∫ t−3
√t
dx=
20
3
4
9 9 9 1 9 −1
3 1 3
3√t
1 3
t2 3 t2 3t2
− +C= −6 t 2 + C= −6 √ t +C
3 1 2 2
2 2
]
9
3 √t
9 3
∫ t−3 dx= −6 √t +C
4 √t 2 4
( 3√9
−6 √ 9 − √ −6 √ 4 )( )
3 3
3 4
2 2
20
3
19. M
∫ ( 10 x 2−13 x−3 ) dx
0
1 1
1 4 4
10∫ x dx−13 ∫ xdx−∫ 3 dx
2
0 1 1
3 2
10 x x
− −3 x +C
3 2
]
1 1
10 x 3 x 2
∫ ( 2 x−3 ) ( 5 x+1 ) dx= 3 − 2 −3 x +C
0 0
( )( )
3 3
10(1) 12 10(0) 02
− −3(1) − − −3(0)
3 2 3 2
−37
6
20. M
( )
3
2 x 3−4 x 2+5 10
∫ x
2
dx=
3
1
( ) ( )
3 3 3
( )
3 2 3 2
2 x −4 x +5 2x 4 x 5 5
∫ x
2
dx=∫ 2 − 2 + 2 dx=∫ 2 x−4+ 2 dx
x x x x
1 1 1
3 3 3 3 3 3
∫ ( 2 x ) dx−∫ ( 4 ) dx+∫
1 1 1
( )
5
x
2
dx=2 ∫ ( x ) dx −∫ ( 4 ) dx +5 ∫ ( x ) dx
1 1 1
−2
2 x2 5 x−1 5
−4 x + +C=x 2−4 x− + C
2 −1 x
( ) ]
3 3 2 3
2 x −4 x +5 5
∫ x
2
2
dx= x −4 x− +C
x
1 1
10
3